IMPLEMENTASI PENGELOLAAN DATA TERPADU KESEJAHTERAAN SOSIAL (DTKS) OLEH DINAS SOSIAL KABUPATEN GRESIK - Rohim, Ahmad Bagus; Priambodo, Bayu (Jurnal Progress Administrasi Publik, 2024)
Digitalization has become a part of life for all countries on this earth, including Indonesia. Digitalization has also penetrated all aspects of life in Indonesian society, making the government also participate in using digitalization in issuing policy products. One of the products of the government is the existence of Integrated Social Welfare Data (DTKS) under the auspices of the Ministry of Social Affairs of the Republic of Indonesia. Where the data contains poverty data collection for each region in Indonesia to facilitate the government in providing social assistance to people in need. This research wants to discuss how the implementation of DTKS management in Gresik Regency according to David C. Corten consists of program, organization, and beneficiary variables. This research uses a descriptive qualitative method with a research location at the Gresik Regency Social Service using primary data collection techniques in the form of interviews and observations, while secondary data in the form of utilizing the results of previous research with different locus. It was found that in its implementation, the Gresik Regency Social Service can implement DTKS management in accordance with the direction.  Even so, in the organizational variables, there are still some obstacles that are often faced, such as several DTKS data holder operators at the urban village level who started to resign due to several reasons such as age, mutation, and so on.   Keywords: Implementation; Welfare; Social; Digitization